2003
DOI: 10.1002/ajmg.a.20276
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked hypohidrotic ectodermal dysplasia mutations in Brazilian families

Abstract: X-linked hypohidrotic ectodermal dysplasia (XLHED) is characterized by severe hypohidrosis, hypotrichosis, and hypodontia. The gene responsible for this pleiotropic syndrome (ED1) consists of 12 exons, 8 of them coding for a transmembrane protein (ectodysplasin-A; EDA-A) involved in the developmental process of epithelial-mesenchymal interaction. ED1 mutations that cause alterations in this protein lead to the XLHED phenotype. The major objective of the present study was to detect ED1 mutations in four Brazili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
1
17
1
1
Order By: Relevance
“…Consistent with these data, truncated EDA-A1 and EDA-A2, which also lacked the amino acids encoded by exon 4 still bound to their specific receptors and activated NF-κB, and truncated EDA-A1 could rescue part of the Tabby phenotype (Yan et al, 2000;Schneider et al, 2001;Koppinen et al, 2001;Gaide and Schneider, 2003). Furthermore, no mutations in exon 4 have been reported to cause human X-linked anhidrotic ectodermal dysplasia patients (Hashiguchi et al, 2003;Visinoni et al, 2003).…”
Section: Discussionsupporting
confidence: 69%
“…Consistent with these data, truncated EDA-A1 and EDA-A2, which also lacked the amino acids encoded by exon 4 still bound to their specific receptors and activated NF-κB, and truncated EDA-A1 could rescue part of the Tabby phenotype (Yan et al, 2000;Schneider et al, 2001;Koppinen et al, 2001;Gaide and Schneider, 2003). Furthermore, no mutations in exon 4 have been reported to cause human X-linked anhidrotic ectodermal dysplasia patients (Hashiguchi et al, 2003;Visinoni et al, 2003).…”
Section: Discussionsupporting
confidence: 69%
“…Hypohidrotic ectodermal dysplasia is characterized most notably by abnormal sweat glands (hypohidrosis), decreased hair development (hypotrichosis), and abnormal dentition (hypodontic) with cases of X-linked, autosomal dominant, and autosomal recessive heredity (10,11). Hypohidrotic ectodermal dysplasia syndrome accounts for this patient's hypodontia with absent teeth, hypotrichosis of her scalp and pubic hair, abnormal palate angle, and dysmorphic ears.…”
Section: Discussionmentioning
confidence: 95%
“…Mutations in EDA are known to cause ectodermal dysplasia (OMIM 305100), a clinical condition characterized by hypotrichosis (sparseness of scalp and body hair), hypohidrosis (reduced ability to sweat), and hypodontia (congenital absence of teeth). More than 64 mutations in the EDA gene have been identified in association with ED (Visinoni et al 2003), but EDA is rarely reported as being implicated in isolated tooth agenesis (Tao et al 2006;Tarpey et al 2007). The EDA is a type II transmembrane protein containing a small N-terminal intracellular part and a larger C-terminal extracellular part.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatograms were analyzed using Sequencher v.4.1.2 (Gene Codes Corporation). Primers and sequencing conditions have been described previously (Visinoni et al 2003). Informed consent was obtained from all individuals who participated in this study.…”
Section: Subjectsmentioning
confidence: 99%